Using ChatGPT – a turning point for vocational schools? - Bader, Christina [Verfasser]; Zellhahn, Sandra [Verfasser] (My University, 2024)
"This article was written by humans. In an era of ChatGPT and similar applications, it seems highly appropriate to clarify what previously was considered a matter of course. One of the reasons for doing so is the increasing blurring of the boundaries between content which is produced by humans and machine-optimised output. The article uses a practical example to highlight the possible areas of deployment of ChatGPT and to show the preparation of stakeholders at Bamberg Upper Vocational School (FOS/BOS) in Bavaria." (authors' abstract; BIBB-Doku)
Keywords: S 3.1 Berufsbildende Schulen; 370; Berufsbildende Schule; Künstliche Intelligenz; Unterrichtsvorbereitung; Lernprozessbegleitung; Kompetenzentwicklung; ChatGPT